Correction: Study protocol of the ASTOP trial: A multicenter, randomized, double-blind, placebo-controlled trial of presurgical aspirin administration for the prevention of thromboembolic complications of coil embolization for ruptured aneurysms. - Sakyo Hirai; Kyohei Fujita; Shoko Fujii; Satoru Takahashi; Keigo Shigeta; Jun Karakama; Yukiko Enomoto; Yohei Sato; Masataka Yoshimura; Shin Hirota; Tatsuya Mizoue; Yoshikazu Yoshino; et al. (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0310906.].